Current treatment options for leptospirosis: a mini-review - Petakh, Pavlo; Behzadi, Payam; Oksenych, Valentyn; Kamyshnyi, Oleksandr (Frontiers in Microbiology, 2024)
Leptospirosis, one of the most common global zoonotic infections, significantly impacts global human health, infecting more than a million people and causing approximately 60,000 deaths annually. This mini-review explores effective treatment strategies for leptospirosis, considering its epidemiology, clinical manifestations, and current therapeutic approaches. Emphasis is placed on antibiotic therapy, including recommendations for mild and severe cases, as well as the role of probiotics in modulating the gut microbiota. Furthermore, novel treatment options, such as bacteriophages and newly synthesized/natural compounds, are discussed, and the findings are expected to provide insights into promising approaches for combating leptospirosis.